PALM OIL REPLACEMENT BY KEPAYANG OIL (Pangium edule Reinw) IN DIETS ON THE QUAIL GROWTH PERFORMANCES - Wiwaha Anas Sumadja; A Azis; C. A. Damayanti (Wahana Peternakan, 2023)
ABSTRACT Currently, the utilization of palm oil as a feed ingredient competes with human needs; thus, we must explore new sources of oil that may be used as alternative feed. Kepayang oil is a new form of feed oil due to its high content of unsaturated fatty acids, which helps in quail growth. The goal of this investigation is to see how replacing palm oil in rations with kepayang oil affects quail growth. The study used 200 female quail 21 days old, kepayang oil, commercial palm oil, mineral mix, maize meal, fish meal, bran, soy cake, lysine, methionine, and 20 units of the quail's cage "battery" type. The investigation used a block randomized design (BRD) with four treatments and five groups, each with a different level of palm and kepayang oil. If the treatment has a significant effect, the Duncan multiple test should be performed. We discovered that replacing palm oil in quail diets with kepayang oil reduced feed intake but had no significant effect on quail weight gain (P > 0.05). Furthermore, incorporating 3% kepayang oil into the quail diet had no effect on the feed efficiency ratio or day of first laying (P > 0.05). As a consequence, between the ages of 21 and 49 days, palm oil can be replaced with kepayang oil up to 3% of the total ration with no negative effects on feed intake, body weight gain, feed efficiency, or the age of the first egg laid. Keywords: Palm Oil, Kepayang Oil, Quails and Growth